Diskusi Mengenai Pemanfaatan Kombucha Bunga Telang Kepada Siswi SMAN 5 Cilegon Banten Sebagai Minuman Probiotik Pengendali Emosi Ketika Datang Bulan - Firman Rezaldi; Arti Wahyu Utami Arti Wahyu Utami; Sugiono Sugiono Sugiono Sugiono; Ipul Saifullah Ipul Saifullah; Maskun Kurniawan Maskun Kurniawan; Rizal Rohmatulloh Rizal Rohmatulloh; Misbakhul Munir Misbakhul Munir (Jurnal Igakerta, 2024)
Puberty is a transition from childhood to adolescence. Menstruation is a painful condition experienced by every woman in quite severe conditions which can result in obstacles to every daily routine. Pain during menstruation can ideally trigger an emotional increase that is quite uncontrollable, so that apart from needing spiritual self-control, physical control is needed by providing fermented biotechnology products in the form of telang flower kombucha which has been widely proven as a probiotic drink that can improve the system. immunity, inhibits microbial growth, wards off free radicals, prevents the growth of cancer cells. Teenagers who study at SMAN 5 Cilegon, especially those involved in KIR (Youth Scientific Work) activities in the field of biology, have learned a lot about the potential of butterfly pea flower kombucha in health, pharmaceutical, agricultural and livestock aspects from a series of presentations on community service materials in 2023, so that there is In collaboration with schools and biology teachers, KIR supervisors have facilitated the use of butterfly pea flower kombucha as a probiotic drink to control emotions during menstruation. This has been proven based on bivariate analysis through the results of the respective T tests both before intervention and post intervention, obtaining a p value of less than 0.005, indicating that H0 is rejected while Ha is accepted, so there is a significant influence on telang flower kombucha after being given in controlling emotions when period.